Aerobic Dance Circuit Training Improves Body Fat Percentage of Obese Female College Undergraduates - Ajayi, Olusegun Adewale; Moses, Monday Omoniyi (Journal of Health Promotion, 2024)
Although the efficacy of aerobic dance has been reported, further insight into the influence of aerobic dance circuit training will provide specific therapy to tame obesity pandemic. Therefore, this study establishes that aerobic dance and circuit-training program (ADCT) improves the body fat percentage of obese female College of Education (COE) students while moderating for age and class of obesity. The study adopted the pretest-posttest control group quasi-experimental design. Seventy obese female undergraduate students (mean age = 21.10±2.46 years) of two COE were purposively selected. The obesity percentage distribution of the participants was class 1 (21.4%), class 2 (60.0%), class 3 (17.1%) and class 4 (1.4%). The participants were randomly assigned to ADCT (N=35) and control (N=35) groups. ADCT lasted 12 weeks, three days (evening), and 40 minutes per session. Body fat percentage was measured pre and post in two groups. Data were analysed using Cochran Q test and Analysis of covariance at 0.05 level of significance. There was significant mean difference in pre-and post-ADCT value of body fat percentage (16.89±4.10>14.96±3.70). There was no significant 3-way interaction effect between Treatment, Age and Class of obesity (F(13,57 = 5.912, P>0.05, 2 = .0.013). Aerobic dance circuit training reduced body fat percentage in obese students. Regular and monitored aerobic dance circuit training significantly improves the health and quality of life of obese female students regardless of age and class of obesity